Energy management for parallel HEV based on PMP algorithm - Zhang, Ning; Ma, Xianghua; Jin, Liming (ICRAE 2017 : 2017 2nd International Conference on Robotics and Automation Engineering : December 29-31, 2017, Shanghai, China, 2017)
The energy crisis and increasingly serious environmental pollution are pressing people to save energy and reduce emissions. Hybrid electric vehicles (HEVs) have demonstrated the capability to improve fuel economy and emissions. Energy management system (EMS) of Hybrid Electric Vehicles can take advantage of maximum electric energy in order to reduce fuel consumption and emission. However, because of the characteristic of nonlinear and hybrid property, it is hard to establish the mathematic model of the EMS of HEVs. Moreover, for the driving cycles are random and the driver's driving habit is different from each other, the difficulty to allocate the request power in real time is greatly increased. An optimization approach based on Pontryagin's Minimum Principle (PMP) is proposed. Through the proposed method, the request power can be allocated between energy resources in real time on the basis of the optimal operation profile of the generator at the special driving cycles, in order that the real-time performance of HEVs can be satisfied and the global optimization of EMS can be guaranteed as well. The ADVISOR simulation results show the proposed energy optimal management method based on Pontryagin's Minimum Principle is valid.